The glycosaminoglycan-binding chemokine fragment CXCL9(74–103) reduces inflammation and tissue damage in mouse models of coronavirus infection - Oliveira, Vivian Louise Soares; Queiroz-Junior, Celso Martins; Hoorelbeke, Delphine; Santos, Felipe Rocha da Silva; Chaves, Ian de Meira; Teixeira, Mauro Martins; Russo, Remo de Castro; Proost, Paul; Costa, Vivian Vasconcelos; Struyf, Sofie; Amaral, Flávio Almeida (Frontiers in Immunology, 2024)
Pulmonary diseases represent a significant burden to patients and the healthcare system and are one of the leading causes of mortality worldwide. Particularly, the COVID-19 pandemic has had a profound global impact, affecting public health, economies, and daily life. While the peak of the crisis has subsided, the global number of reported COVID-19 cases remains significantly high, according to medical agencies around the world. Furthermore, despite the success of vaccines in reducing the number of deaths caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), there remains a gap in the treatment of the disease, especially in addressing uncontrolled inflammation. The massive recruitment of leukocytes to lung tissue and alveoli is a hallmark factor in COVID-19, being essential for effectively responding to the pulmonary insult but also linked to inflammation and disease in the lungslung damage. In this context, mice models are a crucial tool, offering valuable insights into both the pathogenesis of the disease and potential therapeutic approaches. Here, we investigated the anti-inflammatory effect of the glycosaminoglycan (GAG)-binding chemokine fragment CXCL9(74- 103), a molecule that potentially decreases neutrophil transmigration by competing with chemokines in for GAG-binding sites, in two models of pneumonia caused by coronavirus infection. Using In a murine model of betacoronavirus MHV-3 infection, the treatment with CXCL9(74-103) decreased the accumulation of total leukocytes, mainly neutrophils, to the alveolar space and improved several parameters of lung dysfunction 3 days after infection. Additionally, this treatment also reduced the lung damage. In the SARS-CoV-2 model in K18-hACE2-mice, CXCL9(74-103) significantly improved the clinical manifestations of the disease, reducing pulmonary damage and decreasing viral titers in the lungs. These findings indicate that CXCL9(74-103) resulted in highly favorable outcomes in controlling pneumonia caused by coronavirus, as it effectively diminishes the clinical consequences of the infections and reduces both local and systemic inflammation.